Pengaruh belanja modal, investasi dan upah minimum terhadap pertumbuhan ekonomi melalui kesempatan kerja di Kabupaten Batanghari - Gery Hermawan; Erfit Erfit; Purwaka Hari Prihanto (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2021)
This study aims to: 1) determine and analyze the effect of capital expenditure, investment, and minimum wage on employment opportunities in Batanghari Regency and 2) determine and analyze the effect of capital expenditure, investment, and minimum wage on economic growth through employment opportunities in Batanghari Regency. Based on the results of multiple linear regression that partially investment variables have a significant effect on employment opportunities. In contrast, capital expenditures and minimum wages have no significant effect on employment opportunities in Batanghari Regency. Based on the results of multiple linear regression that partially, the minimum wage and employment opportunities have a substantial effect on economic growth, while capital expenditure and investment variables have no significant effect on economic growth in Batanghari Regency.  Keywords: Capital expenditure, Investment, Minimum wage, Employment opportunity, Economic growth.